2004
DOI: 10.1074/jbc.m402475200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated Specific Cleavage of Human Histone Deacetylase 4

Abstract: Histone deacetylase 4 (HDAC4) is a class II HDAC implicated in controlling gene expression important for diverse cellular functions, but little is known about how its expression and stability are regulated. We report here that this deacetylase is unusually unstable, with a half-life of less than 8 h. Consistent with the instability of HDAC4 protein, its mRNA was also highly unstable (with a half-life of less than 4 h). The degradation of HDAC4 could be accelerated by exposure of cells to ultraviolet irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 47 publications
3
82
0
Order By: Relevance
“…We then determined the subcellular localization of endogenous HDAC4 in colon cancer cells by immunofluorescence analysis. Consistent with reports in other cell types (Wang and Yang, 2001;Liu et al, 2004), HDAC4 expression in the HCT116 colon cancer cell line was observed in both the nucleus and cytoplasm (Supplemental Figure 1B). In contrast, the class I HDAC HDAC1 exhibited an exclusively nuclear staining pattern, whereas localization of the class IIb HDAC HDAC6 was predominantly cytoplasmic, consistent with previous studies (Hubbert et al, 2002;Waltregny et al, 2004).…”
Section: Robust Hdac4 Expression In Normal Intestine and In Colon Cansupporting
confidence: 79%
See 1 more Smart Citation
“…We then determined the subcellular localization of endogenous HDAC4 in colon cancer cells by immunofluorescence analysis. Consistent with reports in other cell types (Wang and Yang, 2001;Liu et al, 2004), HDAC4 expression in the HCT116 colon cancer cell line was observed in both the nucleus and cytoplasm (Supplemental Figure 1B). In contrast, the class I HDAC HDAC1 exhibited an exclusively nuclear staining pattern, whereas localization of the class IIb HDAC HDAC6 was predominantly cytoplasmic, consistent with previous studies (Hubbert et al, 2002;Waltregny et al, 2004).…”
Section: Robust Hdac4 Expression In Normal Intestine and In Colon Cansupporting
confidence: 79%
“…The HDAC4 protein comprises 1084 amino acids, with a nuclear localization signal (NLS) located at the amino terminus (amino acids [aa] 244 -279), a catalytic HDAC domain (aa 621-1040), and a nuclear export signal (NES) (aa 1044 -1069) located at the carboxy terminus (Wang and Yang, 2001;Liu et al, 2004). A schematic diagram is shown in Figure 7A.…”
Section: Hdac4 Represses P21 Transcription In Colon Cancer Cellsmentioning
confidence: 99%
“…There is little structural change in the four-helix bundle between the wild type and the His97Phe mutant. Previous studies have shown that the N-terminal domain of HDAC4 containing the glutamine-rich sequence can repress MEF2-dependent transcription independently of the C-terminal catalytic domain (8)(9)(10). Whereas the His97Phe mutant similarly repressed MEF2-dependent transcription, the Phe93Asp mutant showed decreased ability to repress MEF2-dependent transcription (L.G.…”
Section: Resultsmentioning
confidence: 99%
“…Class II HDACs, which include HDAC4, HDAC5, and HDAC9, contain an additional N-terminal extension that confers responsiveness to calcium signals and mediates interactions with transcription factors and cofactors (4)(5)(6)(7). A prominent feature of this Nterminal region is a highly conserved glutamine-rich domain that can repress transcription independently of the C-terminal catalytic domain (8)(9)(10).…”
mentioning
confidence: 99%
“…The adapter domain of class IIa HDACs contains specific residues that are subjected to various posttranslational modifications, such as proteolytic cleavage (Bakin and Jung, 2004;Liu et al, 2004;Paroni et al, 2004), ubiquitination , sumoylation (Kirsh et al, 2002;Petrie et al, 2003) and most importantly phosphorylation. In response to various stimuli, a set of serine residues in the adapter domain of class IIa HDACs is phosphorylated, creating docking sites for the 14-3-3 proteins (Grozinger and Schreiber, 2000;Wang et al, 2000).…”
Section: Structure Of Class Iia Hdacs: the N-terminal Adapter Domainmentioning
confidence: 99%